Zika virus infection in pregnant women in Honduras: study protocol. Issue 1 (December 2016) - Buekens, Pierre; Alger, Jackeline; Althabe, Fernando; Bergel, Eduardo; Berrueta, Amanda; Bustillo, Carolina; Cafferata, Maria-Luisa; Harville, Emily; Rosales, Karla; Wesson, Dawn; Zuniga, Concepcion
Abstract Background Although there is increasing evidence for a relationship between symptomatic Zika virus (ZIKV) maternal infection, and microcephaly, a firm causal relation has yet to be established by epidemiologic studies. Studies also need to be conducted in recently infected settings. Our objectives are to assess the frequency of ZIKV infection during pregnancy in Honduras and the association of microcephaly with ZIKV infection. Methods/Design We will perform a prospective study enrolling pregnant women at their first antenatal visit and following them up until delivery. At the time of enrollment, women will be interviewed to collect socio-demographic data, data needed to locate them for potential additional follow-up, and data about ZIKV symptoms during pregnancy. We will also collect maternal blood as soon as possible after enrollment. A probable maternal ZIKV infection will be defined as positive for maternal ZIKV IgM. A confirmed maternal ZIKV infection will be defined as positive for ZIKV IgM confirmed by plaque reduction neutralization test. Microcephaly at birth will be defined as an occipito-frontal circumference <2SD for sex and gestational age. Our objective is to enroll 2000 pregnant women. In a first step, we will follow a case cohort design and only analyze blood samples for cases and a sub-cohort of 200 women randomly selected. Blood samples for the entire population will be analyzed at a later stage if funds are available. Discussion This protocol was designed to be implemented with minimal resources. It allows a cohort to be built, which could be a foundation for future in-depth and follow-up studies.